Analytical and Computational Results for Neutral Impulsive Fractional System on Time Scales - Navajothi, V. Emimal; Selvi, S.; Akgul, Ali (Contemporary Mathematics, 2024)
This paper delves into the existence and uniqueness of neutral fractional integro-differential impulsive dynamic equations across various time scales, enriched by nonlocal initial conditions using the Caputo-Nabla derivative. By leveraging the refined fixed point theorem, the study provides a robust framework for establishing existence. The theoretical findings are elegantly illustrated through detailed graphical representations, enhancing the comprehension and appeal of the results.